2002
DOI: 10.1021/jf011586r
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Human Salivary Enzymes on Odorant Concentration Changes Occurring in Vivo. 1. Esters and Thiols

Abstract: The influence of human whole saliva on odor-active esters and thiols was investigated. Special emphasis was placed on food-relevant concentrations of the odorants. It was found that the amounts of the esters were reduced during incubation with saliva to different extents according to their chemical structures. Considerable degradations were also observed for 2-furfurylthiol, 2-phenylethanethiol, and 3-mercapto-3-methyl-1-butanol, being reduced from approximately 70 to 20% of their initial concentrations within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
128
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 130 publications
(138 citation statements)
references
References 35 publications
7
128
0
3
Order By: Relevance
“…in the development of the aftertaste of specific foods Hussein, Kachikian, & Pidel, 1983). It has also been shown that the concentrations of some odorants remain unchanged when exposed to saliva, whilst the amounts of potent thiols such as 2-furfurylthiol, which is an aroma constituent of coffee, decreases relatively rapidly (Buettner, 2002a(Buettner, , 2002b. Furthermore, Starkenmann et al found that odorants can be formed from non-odorous precursors (cysteine-S-conjugates), which are stable in aqueous solutions but decompose rapidly in the presence of saliva, thereby releasing potent thio-odorants (Starkenmann, 2003;Starkenmann et al, 2008).…”
Section: Salivation and Oral Metabolism Processesmentioning
confidence: 99%
“…in the development of the aftertaste of specific foods Hussein, Kachikian, & Pidel, 1983). It has also been shown that the concentrations of some odorants remain unchanged when exposed to saliva, whilst the amounts of potent thiols such as 2-furfurylthiol, which is an aroma constituent of coffee, decreases relatively rapidly (Buettner, 2002a(Buettner, , 2002b. Furthermore, Starkenmann et al found that odorants can be formed from non-odorous precursors (cysteine-S-conjugates), which are stable in aqueous solutions but decompose rapidly in the presence of saliva, thereby releasing potent thio-odorants (Starkenmann, 2003;Starkenmann et al, 2008).…”
Section: Salivation and Oral Metabolism Processesmentioning
confidence: 99%
“…Aqueous-based delivery systems containing relatively small particles do not require chewing before swallowing. Nevertheless, they are still exposed to changes in environmental conditions within the mouth that may alter their release properties, such as changes in temperature, enzyme activity, dilution, pH, ionic strength, flow profiles, and interactions (Buettner, 2002;Hansson, Leufven, & Van Ruth, 2003;van Ruth, Grossmann, Geary, & Delahunty, 2001). One or more of these factors may be used as potential triggers for the release of encapsulated active components within the mouth.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, one must bear in mind that food aromas can originate from a diversity of substance classes with a broad range of chemical reactivity (Grosch, 2001;Nijssen et al, 1996), being often heavily metabolised in vivo (Buettner, 2002a(Buettner, , 2002bBuettner, 2010;Engel, 2001Engel, , 2002Zeller, Horst, & Rychlik, 2009).…”
Section: Introductionmentioning
confidence: 99%